Deciphering motor dysfunction and microglial activation in mThy1-α-synuclein mice: a comprehensive study of behavioral, gene expression, and methylation changes - McGregor, Brett A.; Raihan, Md. Obayed; Brishti, Afrina; Hur, Junguk; Porter, James E. (Frontiers in Molecular Neuroscience, 2025)
IntroductionGrowing recognition of microglia’s role in neurodegenerative disorders has accentuated the need to characterize microglia profiles and their influence on pathogenesis. To understand changes observed in the microglial profile during the progression of synucleinopathies, microglial gene expression and DNA methylation were examined in the mThy1-α-synuclein mouse model.MethodsDisease progression was determined using behavioral tests evaluating locomotor deficits before DNA and RNA extraction at 7 and 10 months from isolated microglia for enzymatic methyl-sequencing and RNA-sequencing.ResultsPathway analysis of these changes at 7 months indicates a pro-inflammatory profile and changes in terms related to synaptic maintenance. Expression and methylation at both 7 and 10 months included terms regarding mitochondrial and metabolic stress. While behavior symptoms progressed at 10 months, we see many previously activated pathways being inhibited in microglia at a later stage, with only 8 of 53 shared pathways predicted to be directionally concordant. Despite the difference in pathway directionality, 21 of the 22 genes that were differentially expressed and annotated to differentially methylated regions at both 7 and 10 months had conserved directionality changes.DiscussionThese results highlight a critical period in disease progression, during which the microglia respond to α-synuclein, suggesting a transition in the role of microglia from the early to late stages of the disease.